Leaf metabolite profile of the Brazilian resurrection plant Barbacenia purpurea Hook. (Velloziaceae) shows two time-dependent responses during desiccation and recovering - Suguiyama, Vanessa F.; da Silva, Emerson A.; Meirelles, Sérgio T.; Centeno, Danilo d.; Braga, Marcia R. (Frontiers in Plant Science, 2014)
Barbacenia purpurea is a resurrection species endemic to rock outcrops, in Rio de Janeiro, Brazil. It tolerates great temperature variations, which are associated to periods of up to 30 days without precipitation. Using a metabolomic approach, we analyzed, under winter and summer conditions, changes in the leaf metabolite profile (MP) of potted plants of B. purpurea submitted to daily watered and water deficit for at least 20 days and subsequent slow rehydration for 5 days. Leaves were collected at different time points and had their MP analyzed by GC/MS, HPAEC, and UHPLC techniques, allowing the identification of more than 60 different compounds, including organic and amino acids, sugars, and polyols, among others. In the winter experiment, results suggest the presence of two time-dependent responses in B. purpurea under water stress. The first one starts with the increase in the content of caffeoyl-quinic acids, substances with strong antioxidant activity, until the 16th day of water suppression. When RWC reached less than 80% and 70%, in winter and summer respectively, it was observed an increase in polyols and monosaccharides, followed by an increment in the content of RFO, suggesting osmotic adjustment. Amino acids, such as GABA and asparagine, also increased due to 16 days of water suppression. During rehydration, the levels of the mentioned compounds became similar to those found at the beginning of the experiment and when compared to daily watered plants. We conclude that the tolerance of B. purpurea to dehydration involves the perception of water deficit intensity, which seems to result in different strategies to overcome the gradient of water availability imposed along a certain period of stress mainly during winter. Data from summer experiment indicate that the metabolism of B. pupurea was already primed for drought stress. The accumulation of phenolics in summer seemed to be more temperature and irradiance-dependent than on the RWC.